The mischievians - Joyce, William, 1957- (Atheneum Books for Young Readers, 2013)
Dr. Zooper answers questions about life's ordinary puzzles, such as why homework disappears or how a song gets stuck in one's head, by identifying and describing different kinds of Mischievians.